Desenvolvimento de um aplicativo para dimensionamento de redes de ar comprimido no basic4android - CARDOSO, Gabriel do Carmo (2019)
This work aimed to develop a mobile version for the calculation of internal diameters of compressed air tubes, for didactic use in the pneumatic area. The existence of a mobile version facilitates its distribution and increases its reach. The application, called DIPN (Pneumatic Dimensioning), also aims to bring general knowledge about the methods Fialho, Macintyre, Atlas Copco, Worthington and singularity pressure drop. The application was developed using IDE B4A (Basic4Android) from developer Anywhere Softwere. and a modeling was elaborated, with the description of its screens and functionalities. The methodological model used for development is Scrum, in order to provide a quality application, following existing best practices. In addition, software functionality tests were performed. Defects found during the test were fixed and usability improvements were made to improve the user experience. The application proved to be a tool capable of transmitting knowledge, bringing information about such methods and facilitating calculations and final results, responding to their purpose.